GIS tutorial for crime analysis - Gorr, Wilpen L; Kurland, Kristen Seamens, 1966- (Redlands, Calif. : ESRI Press, 2011)
A computer workbook to teach crime mapping and analysis skills using ArcGIS Desktop software. Includes a 180-day trial version of ArcGIS Desktop 10 software and exercise data
-- 1. Working with crime maps -- Introduction to crime mapping and analysis -- Exploring ArcGIS desktop -- Using crime maps -- Designing and building crime maps -- 2. Conducting crime analysis -- Querying crime maps -- Building crime map animations -- Conducting hot spot analysis -- 3. Building a crime mapping and analysis system -- Assembling jurisdiction maps -- Preparing incident data for mapping -- Automating crime maps
Includes bibliographical references
Keywords: ArcGIS; Crime analysis -- Data processing; Geographic information systems; Digital mapping